Normalisasi Data Penjualan Ternak Menggunakan Metode Binning Untuk Menentukan Pola Penjualan Ternak Menerapkan Metode Apriori - Marinus Halawa (Graha Mitra Edukasi, 2024)
To Get Sales Data That Can Be Processed, It is Necessary to Normalize Data Aimed at Obtaining the Desired Information, One of which is by using the Binning Method in Normalizing Sales Data in Livestock. So that the Data That Has Been Processed With The Binning Method Which Is Used As Data In Obtaining Information On Purchasing Patterns Using A priori Algorithms. The problem in this study is that PT Expravet Nasuba does not yet have a system to obtain profit information and break-even points for broiler chicken livestock business with a Partnership Pattern.one of the solutions to the existing problems is to normalize data using the binning method, and then the results of the binning method are processed using the a priori method to obtain information and decision trees. This study aims to find out the profit and profitability point of the Broiler Chicken livestock business with a Partnership Pattern. This research has been carried out in Langge Village and Dunggala Village, Tapa District, Bone Bolango Regency. This research was conducted for 2 months starting from May-July June-August. The method used in this implementation is the case study method, this study describes the source of business capital for broiler chicken farms with a capacity of 2400 and 5000 heads using their own capital. From the results of the research conducted, it can be concluded that the Results of the Application of the A priori Method are able to get the Pattern of Purchasing the Type of Livestock Purchased by Customers Based on the Sport Value Given Where If You Buy White Snapper, You Will Buy Vanami Shrimp and White Pomfret and Other Patterns.